Modeling the light attenuation phenomenon during photoautotrophic growth of A. variabilis ATCC 29413 in a batch photobioreactor - Salleh S.F.; Kamaruddin A.; Uzir M.H.; Mohamed A.R.; Shamsuddin A.H. (John Wiley and Sons Ltd, 2023)
Cell growth; Cells; Cytology; Electromagnetic wave attenuation; Photobioreactors; Automatic monitoring; Cell concentrations; Cyanobacteria; Cyanobacterial cells; Growth modeling; Light attenuation; Photoautotrophic growth; Photobiore-actor; Growth kinetics; Anabaena variabilis; Article; batch reactor; cell growth; light irradiance; microbial growth; model; nonhuman; photoautotroph; photobioreactor; radiation attenuation